The CCK-system underpins novelty-seeking behavior in the rat - Ballaz, Santiago J. (2015)
Cholecystokinin (CCK) and its receptor CCK-2R have been shown to promote emotional responsivity and behavioral sensitization to psych ostimulants in the rat. An animal model has been developed based on locomotor response to a novel inescapable environment. Animals exhibiting consistent differences in locomotor response to novelty have been termed as high and low responder rats (HR and LR, respectively). This paradigm is deemed to model sensation-seeking, a personality trait closely associated with substance abuse. The present study provides genetic and pharmacological evidence that the CCK-ergic system modulates this behavior. Distinctive patterns of CCK-related gene expression in HR and LR animals occurred beyond the mesolimbic pathways. CCK gene expression was higher in hippocampus, amygdala, and prefrontal cortex, but lower in the ventral tegmental area of HR relative to LR rats. Levels of CCK-2R mRNA were more elevated in LR animals in some areas of the forebrain such as the prefrontal cortex, nucleus accumbens, and hippocampus. Additionally, CCK-2R blockade with the antagonist LY225.910 (0.5 mg/kg) removed phenotype differences in sustained exploration of novel stimuli (i.e., a novel-object) in HR and LR rats exposed to an enriched openfield test series. Finally, CCK-2R blockade also altered M-2 and 5-HT7 receptor gene expression in the mediodorsal thalamus (a strategic structure for corticothalamic trafficking) in a phenotype-dependent manner. Taken together, the findings reported here suggest that distinct CCK-ergic function may contribute to promoting individual differences in novelty-seeking behavior. (c) 2008 Elsevier Ltd. All rights reserved.